HUBUNGAN KECERDASAN EMOSIONAL DENGAN PENYESUAIAN PERNIKAHAN PADA WANITA BALI YANG MENJALANI PERNIKAHAN NGEROB DI DENPASAR - Ni Putu Widya Dharma Astasari; Made Diah Lestari (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2017)
Marriage is one of young adulthood’s development tasks. Some problems often arise in the initial period of marriage and disturb the marital adjustment process. In some countries with strong collective culture, a big family involvement is crucial and give an impact to marital adjustment process. In Bali, there is a culture called ngerob. Ngerob is a situation where one of the boys of a family should stay at parents home to continue the obligations and responsibilities of parents in customs, which means that a married man should invite his wife to live in a home with his parents. Adjustment with the partner's family is important in ngerob marriage. In order to reach a success marital adjustment, the wife is expected to have stable emotions. Emotionally intelligent wife is considered to have good self-control, able to express emotions appropriately, so that they can adapt with the circumstances it faces. The aim of this research is to determine the relation between emotional intelligence and marital adjustment among Balinese women who are ngerob in Denpasar. Subjects were Balinese woman who are married, living with in-laws (ngerob) and live in Denpasar (n=60). Data were collected through emotional intelligence questionnaire with and the marital adjustment questionnaire with. The data were analyzed using product moment correlation test. The correlation coefficient between emotional intelligence and marital adjustment are 0.503 with a significance level of 0.000 (p <0.05). The results of this research showed that there is a positive and significant correlation between emotional intelligence and marital adjustment among Balinese women who are ngerob in Denpasar. The higher level of emotional intelligence encourage a better marital adjustment process among Balinese women who are ngerob in Denpasar. Keywords : emotional intelligence, marital adjustment, ngerob